Comparative Analysis of Rapid Diagnostic Test (ICT) and Microscopy for the Diagnosis of Malaria - Farid Ullah, Yasmeen Bibi, Muhammad Arif, Fouzia Nawab, Ayesha Wakil, Syed Luqman Shuaib (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Malaria is caused by four Plasmodium species (vivax, falciparum, Ovale, and Malariae). Malarial parasites can be diagnosed by examining blood smear under microscope, rapid diagnostic test (ICT), and by detecting nucleic acid of parasite using polymerase chain reaction. This study was conducted to find out the diagnostic accuracy of rapid diagnostic test (ICT) in association with microscopy as a gold standard for the detection of malarial parasites P.vivax, P. falciparum and the effect of parasitic load on both diagnostic methods - ICT and light microscopy. Materials & Methods: The study design was cross sectional validation, done at a private clinical set up in Peshawar, Pakistan. Parasite count was performed to quantify parasitic load strictly according to the rules constituted by World Health organization (WHO). Results: A total of 32 patients were identified to be infected with malarial parasites on light microscopy and 68 cases were found negative. Among the positives, P.vivax was detected in 28 cases and P. falciparum in 4 cases. The ICT results showed 29 of the cases positive for malarial parasites and 71 negative. Among the positives, P.vivax was detected in 25 cases, P. falciparum in 2 cases, while 2 cases showed mixed infection. Thus the ICT result for malaria showed 95% sensitivity and 100% specificity with 97% of diagnostic accuracy. The parasitic count was found to be ≤ 208 in those false negative cases on ICT method which showed the impact of low parasitic load on the diagnostic accuracy of ICT method. Key words: Malaria, Plasmodium falciparum, Plasmodium vivax, ICT